REFERENCE DAN SENSE DALAM KIDUNG AGUNG (SUATU ANALISIS SEMANTIK) - Budiman, Eldo; Lasut, Theresia M.C; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Eldo Budiman1Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Dra. Theresia M. C. Lasut, M.Hum2Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Dr. Garryn Ch. Ranuntu, S.Pd, M.Hum3Â  Â  Â  Â  Â  Â This research is entiteled â€œThe References and Sense in sentences used in Song of Songsâ€. The aims of this research are to identify and classify the kinds of references and to analyze and describe the meanings of references and sense in sentences used in Song of Songs. The method used in this research is descriptive method. The data of reference and sense have been taken in sentences from the holy bible with the new international version. The data were analyzed based on Saeedâ€™s (2003), Hurfordâ€™s (2007), and Riemerâ€™s (2010) theories. The result of this research shows there are two kinds of references in Song of Songs, those are constant and variabel reference. Constant reference is an expression that refers to an object only, expressions like Libanon and Damascus are sometimes described as having constant reference. Variable reference is an expression that refers to many references, expressions like I, you, she, he, we, they, us etc are said to have variable reference. Sense may be defined as the general meaning or the concept underlying the word.Keywords : Semantic, Reference, Sense, Constant, Variable, Song of Songs